THE ANALYSIS OF VERBAL AND VISUAL MEANINGS OF ADVERTISMENTS FOUND AT THE NOW BALI MAGAZINE: A SEMANTIC STUDY - Agustia, Tri Sutrisna; Karmini, Luh Ayu Mila (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTThe aim of this study is to analyze the verbal and visual, and type of meanings found inadvertisement at NOW Bali Magazine. This method was conducted using qualitative descriptivemethods. Data were analyzed using 7 types of meaning, Semantic (meaning study) theory by G.Leech (1981), verbal and visual advertising as communication theory by (Dyer 1993). The Resultof this study is taken from 10 data in advertisement. Types of Dominant Meanings is Conceptualmeaning means what the words used refer to. The advertisement uses several words that refer to thebenefits it must capture or to convince consumers.Keywords: Semantics, verbal and visual, advertisements, types of meaningsABSTRAKTujuan dari penelitian ini adalah untuk menganalisis makna verbal dan visual, dan tipe makna yangterdapat pada iklan Majalah NOW Bali. Metode ini dilakukan dengan menggunakan metodedeskriptif kualitatif. Data dianalisis menggunakan tujuh tipe makna, teori Semantik (studi makna)oleh G. Leech (1981). Periklanan verbal dan visual sebagai teori komunikasi oleh (Dyer 1993).Hasil penelitian ini diambil dari sepuluh data dalam iklan. Tipe Makna yang Dominan adalahMakna konseptual yang berarti mengacu pada kata-kata yang digunakan. iklan tersebutmenggunakan beberapa kata yang mengacu pada manfaat yang harus ditangkap atau untukmeyakinkan konsumen.Kata kunci: Semantik, verbal dan visual, iklan, tipe makna.